Book review. The Palgrave Handbook of Women and Science since 1660 - Gotsis, Georgios (Neusis, 2024)
The present collective volume is a decisive contribution to the overview of a wide range of problems that highlight the above problematic, focusing on specific historical episodes, from the time of the Scientific Revolution to the end of the 20th century. It is a collective volume that contributes to the rational reconstruction of disputed phases in the history and historiography of science from the perspective of gender.